PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR GEOGRAFI SISWA KELAS X IPS MAN 2 KABUPATEN KONAWE SELATAN PADA MATERI POKOK LITOSFER - Widiyantoro, Andika Dwi (Universitas Halu Oleo, 2018)
The problems examined are: 1) the description of the learning activities of students 2) Description of activity teaching teacher 3) increase in the results of the study. The research aims to 1) Describe student learning activities, 2) Describes the activity of teaching teachers. 3) Determine the increase in the results of the study. This type of research is Research Action class (RAA) which has been implemented 2 cycle. The subject of this research students are registered on the even-numbered year semester lesson 2016/2017 amounted to 23 people. The data source of this research activity is to teach teachers and learning activities of students obtained from the observation sheet and the results of learning as measured through tests. The data type used is the quantitative and qualitative. The results showed that 1) learning activities at each cycle tends to increase. This is demonstrated by average score on each cycle, on cycle I average score activity students are increasing at 2.7 cycle II be 3.2. cycle I Â 2) on average score 2.7 teacher teaching activity is increased in cycle II be 3.2. Learning Outcome 3) geography enhanced through Contextual learning model of Teaching And Learning (CTL). On cycle I students who complete 12 (52.2%) and not completely and absolutely no 9 (33,33%) with an average of 66 while on the second cycle was increased to 19 (83%) of students who completely and 4 (17%) students do not complete an average of 78.17.